A Persistent Phosphanyl‐Substituted Thioketyl Radical Anion. Issue 9 (12th January 2022) - Szych, Lilian Sophie; Pilopp, Yannic; Bresien, Jonas; Villinger, Alexander; Rabeah, Jabor; Schulz, Axel
Abstract: Alkali metal salts, M + [Ter( i Pr)P−C(=S)−P( i Pr)2 S] .− (M=Na, K; 2 _M ; Ter=2, 6‐bis‐(2, 4, 6‐trimethylphenyl)phenyl) containing a room‐temperature‐stable thioketyl radical anion were obtained by reduction of the thioketone precursor, Ter( i Pr)P−C(=S)−P( i Pr)2 S (1 ), with alkali metals (Na, K). Single‐crystal X‐ray studies as well as EPR spectroscopy revealed the unequivocal existence of a thioketyl radical anion in the solid state and in solution, respectively. The computed Mulliken spin density within 2 _M is mainly located at the sulfur (49 %) and the carbonyl carbon (33 %) atoms. Upon adding [2.2.2]‐cryptand to the radical species 2 _K to minimize the interionic interaction, an activation reaction was observed, yielding a potassium salt with a phosphanyl thioether based anion, [K(crypt)] + [Ter( i Pr)P−C(−S‐ i Pr)−P( i Pr)2 S] − (3 ) as the product of an intermolecular shift of an i Pr group from a second anion. The products were fully characterized and application of the radical anion as a reducing agent was demonstrated. Abstract : A stable thioketyl radical anion formed by reduction of a phosphanylthioketone with alkali metals is presented. The structural and electronic parameters of the products were elucidated, revealing that the spin density in the isolated radicals is mainly localized at the thiocarbonyl C−S unit.